Stacking‐Induced Diamagnetic/Paramagnetic Conversion of Imidazo[1, 2‐a]pyridin‐2(3 H)‐one Derivatives: Near‐Infrared Absorption and Magnetic Properties in the Solid State. Issue 9 (14th June 2013) - Yong, Guoping; Zhang, Xuerui; Zhao, Yumei; She, Wenlong
Abstract Herein, we present three imidazo[1, 2‐a]pyridin‐2(3 H)‐one derivatives that are diamagnetic in solution, but paramagnetic in the solid state, possibly owing to a stacking‐induced formation of phenoxide‐type radicals. Notably, a larger bathochromic shift of the absorption (even up to the near‐ infrared region) of these three compounds was observed in the solid state than in solution, which was attributable to the ordered columnar stacking arrangements or their single‐electron character as radicals in the solid state. Interestingly, compared to that in solution, (E)‐3‐(pyridin‐4′‐ylmethylene)imidazo[1, 2‐a]pyridine 2(3 H)‐one displayed a largely red‐shifted emission (centered at 660 nm, with tailing above 800 nm) in the solid state. A larger bathochromic shift (260 nm) of the emission is an indication of better order and tight stacking in the solid state, which is brought about by the rigid and polar acceptor. These three compounds also reveal different magnetic susceptibilities at 300 K, thus implying that they possess various columnar stacking structures. Most interestingly, these three radicals exhibit unusual ferromagnetic‐to‐antiferromagnetic phase transitions, which can be attributed to anisotropic contraction and non‐uniform slippage of the columnar stacking chains.